Pengukuran minat berdasarkan teori Holland dan keterkaitannya dengan indeks prestasi Mahasiswa Prodi Bimbingan dan Konseling FKIP UNTAN angkatan 2021/ 2022 - Yuline, Yuline (Academy of Education Journal, 2024)
This study aims to see the relationship between interests based on Holland's theory and the GPA of FKIP Untan Counseling Guidance Study Program students for the 2021/2022 academic year. The method used is a quantitative descriptive method and the data collection tool used is a questionnaire adapted from Holland's interest inventory. The population in this study is 44 students of the BK FKIP UNTAN Study Program class of 2021/2022. Data analysis used descriptive statistics with Eta correlation, which resulted in a percentage of student interest score scores. Based on the results of data processing, it was obtained that most students have a dominant type of interest in the social type 65.9% (29 students) in the fairly high category, this shows that students of the Guidance and counseling study program have interests in accordance with the characteristics of work as Bimgingan and Counseling / Counselor teachers at school. The cumulative achievement index for 4 semesters obtained by guidance and counseling students of the class of 2021/2022 is included in the good category with an average of 3.56. The correlation between interest and student IP shows a very strong correlation category with a number of 0.823.